Systematic Lymph Node Dissection May Be Abolished in Patients With Apparent Early-Stage Low-Grade Mucinous and Endometrioid Epithelial Ovarian Cancer - Chen, Jiayu; Yin, Jie; Li, Yan; Gu, Yu; Wang, Wei; Shan, Ying; Wang, Yong-Xue; Qin, Meng; Cai, Yan; Jin, Ying; Pan, Lingya (Frontiers in Oncology, 2021)
Objective To investigate whether systematic lymph node dissection can confer clinical benefits in patients with apparent early-stage low-grade epithelial ovarian cancer. Methods Patients with apparent early-stage low-grade epithelial ovarian cancer seen at Peking Union Medical College Hospital from January 1, 2005, to December 31, 2015, were retrospectively enrolled. Patients with other histological types and those who did not receive necessary adjuvant chemotherapy were excluded. Data collection and long-term follow-up were performed. According to the removed lymph node number, three groups based on surgical methods were used: abnormal lymph node resection, pelvic lymphadenectomy, and systematic lymph node dissection to control surgical quality. Their effects on prognosis were analyzed in pathological subgroups. Results A total of 196 patients were enrolled; 30.1% of patients had serous, 42.3% of patients had mucinous, and 27.6% of patients had endometrioid carcinoma, of which 51 (26.0%), 96 (49.0), and 49 (25.0%) patients were treated with the above surgical methods, respectively. The occult lymph node metastasis rate was 14 (7.1%), and only five (2.6%) of apparent early-stage patients were upstaged due to lymph node metastasis alone. Systematic lymph node dissection did not benefit progression-free survival or disease-specific overall survival of apparent early-stage low-grade mucinous and endometrioid epithelial ovarian cancer but prolonged progression-free survival of apparent early-stage low-grade serous patients (OR, 0.231, 95% CI, 0.080, 0.668, p = 0.007). Conclusions Systematic lymph node dissection may be abolished in patients with apparent early-stage low-grade mucinous and endometrioid epithelial ovarian cancer but may be considered for apparent early-stage low-grade serous patients.